The dynamics of Bovini exploitation strategies on the Central Plains of China from the Middle Neolithic to the Bronze Age - Xiaochen Pei; Fawei Liang; Yanpeng Cao; Yunan Zhang (Scientific Reports)
Abstract Bos and Bubalus are important Bovini resources worldwide and were widely exploited on the Central Plains of China during the Neolithic and Bronze Ages. However, distinguishing between Bos and Bubalus remains were challenging due to their similar morphological traits, which leaves the interaction between them poorly understood. This study is the first to combine Zooarchaeology by Mass Spectrometry (ZooMS) with zooarchaeological methods to identify Bos and Bubalus in China at the Tuchengwang (5600–4300 cal. BP), and Pingliangtai (4200–3900 cal. BP) sites. This was accompanied by carbon and nitrogen isotope analyses of bone collagen to discuss their diets on the Central Plains. Our findings indicate that these exploitation strategies are dynamic. Aurochs (Bos primigenius) and water buffaloes (Bubalus mepistopheles) were exploited before the introduction of cattle (Bos taurus), and this exploitation continued into the Bronze Age. The exploitation of local wild Bovini resources may have influenced the adoption of cattle during the End Neolithic. By this time, cattle predominated in Bovini remains at most sites, but the adoption of cattle was not a phenomenon of unison, and their exploitation strategies became more diverse, especially in ritual practices. Wild water buffaloes had evolved into privilege goods by the Bronze Age, especially during the late Shang. This study contributes to a deeper understanding of human-animal-environment relationships between Bovini and ancient people.